Trends analysis of groundwater: Using non-parametric methods in Terengganu Malaysia - Abdullahi, M.G; Toriman, M.E.; Gasim, M.B.; Garba, I. (2015)
Groundwater is the most essential and reliable source of fresh water in every part of the world including an area with high excessive amount of rainfall and plentiful surface water. The study used Mann-Kendall t-test to analyze the data collected from the seven hydrological stations in Terengganu, Malaysia. This analysis investigated the pattern and trends of the daily groundwater level data. The result of the analysis shows that there is a negative increase in trends for the groundwater level of 2000 to 2012 and the result also indicate that, the most decreases in trends is from the year 2005 to 2009 that is from 130 to 280 in the trend chart. However there is small increases in trend from 2009 to 2012, that is from 280 to 350 in the chart. This result entailed that there is an expectation of increases in trend in the future in the area.